Maize fungal root pathogens as affected by fertilisation and rotation with legumes. (March 2023) - Nemadodzi, Edzisani A.; Franke, Angelinus C.; Mashingaidze, Nester; Kotzé, Elmarie; Mavunganidze, Zira
Abstract: The abilities of grain legumes to fix atmospheric nitrogen are well documented, but the non-N effects of incorporating legumes into cereal-based systems are poorly understood. Continuous cropping of maize is assumed to increase maize fungal root pathogens, but few studies have documented this in sub-Saharan Africa. In this study, it was hypothesized that maize pathogen densities of F. oxysporum, F. verticillioides, F. equiseti, F. graminearum, F. chlamydosporum, C. eragostidis, M. phaseolina, Trichoderma spp., Pythium spp, Phoma spp, R. solani and E.pedicellatum are lower under legume-maize rotations than under continuous maize cropping, while fertilisation also affects pathogen densities. Field measurements were taken during the 2017/18 and 2018/19 summer growing seasons at two sites in South Africa to investigate the effect of crop rotation and fertilisation on densities of soil-borne fungal pathogens in maize. Densities of 12 pathogens on maize roots and crowns were investigated 110 days after planting using a modified DNA extraction method and qPCR technology. Maize following a legume had lower densities of F. graminearum, F. oxysporum, E. pedicellatum, and C. eragostidis at both localities . However, no consistent rotation effects were observed on densities of M. phaseolina, Trichoderma spp., Pythium spp., R. solani, Phoma spp., F. verticillioides and F. equiseti . Impacts of fertilisation on pathogen densities were also inconsistent depending on the site and season. This warrants for an integrated approach to fungal pathogen control in maize production. Highlights: Crop rotation with a grain legume suppresses some maize root fungal pathogens but does not eradicate them. The impact of fertilisation on the suppression of maize root pathogens depends on seasons and localities. Intermittent dry spell followed by high precipitation can favour some fungal pathogens irrespective of cropping system. Effective control of maize root fungal pathogens requires a holistic approach.